Hydroxyurea use in young infants with sickle cell disease. Issue 7 (7th February 2019) - Schuchard, Sarah B.; Lissick, Jennifer R.; Nickel, Amanda; Watson, David; Moquist, Kristin L.; Blaylark, Rae M.; Nelson, Stephen C.
Abstract: Background: Hydroxyurea (HU) reduces complications and improves quality and duration of life in sickle cell disease. Evidence supports the use of HU starting after nine months of age. Procedures: We performed a retrospective study of patients starting HU at less than five years of age between January 1, 2008, and December 31, 2016. We evaluated clinical events, laboratory data, and toxicity between three different age groups: cohort 1 (0–1 year), cohort 2 (1–2 years), and cohort 3 (2–5 years). Results: Sixty‐five patients were included in the analysis. The mean age was 7.2 months ( n = 35), 19.5 months ( n = 13), and 35.5 months ( n = 17) for cohorts 1, 2, and 3, respectively. Cohort 1 had higher hemoglobin ( P = 0.0003) and MCV ( P = 0.0199) and lower absolute reticulocyte count ( P = 0.0304) at 24 months of age compared with cohort 3. The absolute neutrophil count (ANC) was lower compared with both older cohorts ( P = 0.0364, 0.0025). The mean baseline hemoglobin F in cohort 1 was 31.5% compared with 19.7% and 16.5% in cohorts 2 and 3, respectively ( P = 0.002, P < 0.0001). The mean duration of therapy was 31.3 months, 57.6 months ( P = 0.018), and 29.1 months ( P = 0.401), respectively. Mean Hb F levels remained higher in cohort 1 (29.9%) compared with cohorts 2 and 3 (20.4%, P = 0.007; 20.6%, P = 0.003). Cohort 1 experienced fewer hospitalizations ( P = 0.0025), pain crises ( P = 0.0618), and transfusions ( P = 0.0426). There was no difference in toxicity between groups. Conclusion: HU is safe and effective in patients 5 to 12 months of age and generated a more robust response compared with initiation in older patients.